Nigeria’s Foreign Policy Objectives and National Question: Assessing Implementation and Challenges - Umar, Ado; Muyiwa, Okunola O.; Umar, Mohammed; Dung, Kim Luka (Kashere Journal of Politics and International Relations, 2023)
Foreign policy is concerned with the development, security, actualization, and promotion of a country’s national interests. This paper focuses on the implementation of Nigeria’s foreign policy aims in tandem with domestic objectives of addressing several ’National problems’ themes such as insecurity, revenue sharing, resource control, underdevelopment, insurgency, ethnic and religious upheavals, and so on. Secondary sources of data such as textbooks, journals, newspapers, and online resources were used to gather data for the paper. The results of the study indicate that there are difficulty in implementing Nigeria’s foreign policy since the emphasis was on addressing continental and global issues rather than domestic ones. The study recommends a new approach to Nigeria’s foreign policy initiative in order to solve the National Questions. As a result, it is proposed that in order for Nigeria to reap the benefits from its foreign policy, it should concentrate and reformulate its foreign policy only on national interests rather than through the lens of African-centered policy or global one. It also advocates the urgency for the Nigerian state to address the economic challenge facing Nigerians, the situation exacerbated by the recent fuel subsidy removal by the recently inaugurated federal administration; this would significantly reduce the degree of insecurity in the country, and when security and social life improve, it will strengthen Nigeria’s standing in the international community.